A diptych reading of Christ's transfiguration: trans and intersex aesthetics reveal baptismal identity. Issue 1 (4th May 2019) - Wolff, Michelle
ABSTRACT: The synoptic Gospels describe Jesus Christ's transfiguration not as a mode of ontological change, but rather as a means of revelation – that he is the second person of the Trinity. Through a diptych reading of Christ's transfiguration and crucifixion, I argue that those who experience hate crimes share in Christ's misrecognition in the midst of revealing truth, which can result in violence and death. Additionally, I offer a constructive, biblical theology of trans and intersex aesthetics that runs counter to neoliberal identity politics by illuminating how the bodily presentation of trans and intersex persons of faith reveal a baptismal truth – that through Christ humanity is adopted as co-heirs with him.